Malaria eradication in armed conflict: public health measures developed during the Sri Lankan Civil War - Dr. Sonia Michael,; Dr. Dc Samarata, (Al-Qanṭara, 2022)
This article aims to detail the four tactics used in Sri Lanka to overcome the aforementioned challenges and eventually eradicate malaria. The first strategy was disease assistance from the Sri Lankan government and the Liberation Front. Despite the country's 26-year civil war, the World Health Organization declared Sri Lanka malaria-free in 2016. Nearly 30 years of malaria elimination efforts in Sri Lanka culminated in this success after the last major outbreak. Malaria resurfaced in the years 1986-1987, with 600,000 cases discovered. These efforts were hampered by a lack of medical personnel in conflict zones, a breakdown in vector control operations, gaps in the medication supply chain, and an increase in malaria cases among the displaced.